Challenges of Building a Jordanian Knowledge Society - Abu hamoud, Muwafaq M.; Alkhatib , Walid M. (Dirasat: Human and Social Sciences, 2023)
Objectives: The study addressed the challenges of building the Jordanian knowledge society from a student perspective and aims to clarify their perceptions and preconceptions in relation to the building of this society. Methods: The study adopted the descriptive analytical approach in collecting information and data that interprets, analyzes, and describes the reality and current situation of the subject of study. A random sample, consist of 311 of bachelor students in Philadelphia University, were selected. Results: The study revealed that the members of the study sample are aware of the concept of a knowledge society in which the society employs knowledge and information to enhance the creative and innovative abilities and skills of individuals. A significant percentage of the study sample does not know that the political system plays the largest role in building a knowledge society, and that the economy is the decisive factor in its construction. Conclusion: The study recommends building clear national programs, projects, and visions to spread community awareness of the importance of building a knowledge society and its requirements, and the need to activate the real partnership between all national institutions and sectors, supported by real political will, to ensure that the requirements of the knowledge society are met.